Motivation and Learning Conceptions That Matter When Considering Global Citizenship Education: Global Citizenship Education - Iborra Cuéllar, Alejandro; BRUNO, LUANA; García-Varela, Ana Belén (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
35 undergraduate students enrolled in a Primary Education Program participated in an innovation activity consisting of creating an ideal school and promoting a global citizenship education. The students completed a survey in which they evaluated the lesson they received from their peers in terms of motivation and the type of activities carried out in terms of the learning conception promoted. We followed a quasi-experimental pre-test-post-test design using a Wilcoxon signed-rank test. Results observed a significant increase in only in meaning motivation. Athough no significant shifts in learning conceptions were found, there was a trend toward interactive and applicative learning approaches.